Intertemporally Dependent Preferences and the Volatility of Consumption and Wealth - Sundaresan, Suresh M. (Review of Financial Studies, 1989)
[In this article we construct a model in which a consumer's utility depends on the consumption history. We describe a general equilibrium framework similar to Cox, Ingersoll, and Ross (1985a). A simple example is then solved in closed form in this general equilibrium setting to rationalize the observed stickiness of the consumption series relative to the fluctuations in stock market wealth. The sample paths of consumption generated from this model imply lower variability in consumption growth rates compared to those generated by models with separable utility functions. We then present a partial equilibrium model similar to Merton (1969, 1971) and extend Merton's results on optimal consumption and portfolio rules to accommodate nonseparability in preferences. Asset pricing implications of our framework are briefly explored.]